Sustainability of ARV provision in developing countries: challenging a framework based on program history - Thiago Botelho Azeredo (Ciência & Saúde Coletiva)
Abstract The provision of ARVs is central to HIV/AIDS programs, because of its impact on the course of the disease and on quality of life. Although first-line treatments costs have declined, treatment-associated expenses are steeper each year. Sustainability is therefore an important variable for the success of treatment programs. A conceptual framework on sustainability of ARV provision was developed, followed by data collection instruments. The pilot study was undertaken in Brazil. Bolivia, Peru and Mozambique, were visited. Key informants were identified and interviewed. Investigation of sustainability related to ARV provision involved implementation and routinization events of provision schemes. Evidence of greater sustainability potential was observed in Peru, where provision is implemented and routinized by the National HIV/AIDS program and expenditures met by the government. In Mozambique, provision is dependent on donations and external aid, but the country displays a great effort to incorporate ARV provision and care in routine healthcare activities. Bolivia, in addition to external dependence on financing and management of drug supply, presents problems regarding implementation and routinization. The conceptual framework was useful in recognizing events that influence sustainable ARV provision in these countries.